Sealing Reliability and Sensitivity Analysis for a Premium Threaded Connection Based on Kriging Model - 郭伟 崔卫民 何勃 刘敬一 宋笔锋 (东华大学学报（英文版）, 2016)
In order to analyze the sealing performance of a new designed premium threaded connection,this paper studies the sealing reliability and sensitivity of the premium threaded connection at its most dangerous load condition based on Kriging model.The load condition of premium threaded connection in deep well is so complex that the most dangerous load point of premium threaded connection under the typical series loads is studied by finite element analysis（FEA） method firstly.Since the FEA of the premium threaded connection is too time-consuming,Kriging model which is accurate and efficient for multidimensional and highly nonlinear problems is built to calculate the sealing reliability of the premium threaded connection at the most dangerous load point.Finally,the sealing sensitivity analysis of the premium threaded connection is performed by the method of variance-based global sensitivity analysis.The work in this paper could contribute for the analysis and further improvement of the premium threaded connection.